A Survey among Plastic Surgeons Wearing a Mask in Operating Room - Ahmad, Muhammad (World J Plast Surg, 2019)
BACKGROUND: Face mask is considered to be an integral part of a surgeon’s dress in operating room. The following study was carried out among the plastic surgeons to know their views about the wearing the face masks in operating room (OR). METHODS: A questionnaire was developed and was sent to the 2 groups of plastic surgeons which included 8 questions. Group A consisted of 100 plastic surgeons from the subcontinent. Group B consisted of 100 plastic surgeons of USA and European origins. The questionnaires were sent by emails and the data was analyzed. The questionnaire was consisted of 8 questions. RESULTS: About 93% of the plastic surgeons in group A wore the mask and 86% in group B. About 96% of plastic surgeon in group A and 99% in group B used disposable masks and only 4% in group A and 1% in group B used re-usable/washable face masks. About 59% in group A and 63% in group B covered the nose. Botox and filler injections were the commonest procedures in which the surgeons opted to perform without face mask (74% in group A and 68% in group B), followed by liposuction (41% in group A and 34% in group B). The majority in both groups believed that face mask decreases the surgical site infection. CONCLUSION: Most of the plastic surgeons wore the face masks in the OR. Care must be taken to ensure that properly designed studies that determine if surgical masks prevent post-operative wound infection.